Fiction et histoire dans Les Onze de Pierre Michon - Souad Yacoub Khlif (Itinéraires)
Pierre Michon’s Les Onze offers itself to be read as both an imaginary life and a meditation on art and history. In this text, the story of a painter, François-Élie Corentin, is intertwined with that of the French Revolution. This fusion takes place through the description of a large painting, which would be exhibited in the Louvre, representing the eleven members of the Comité de salut public (Committee of Public Safety) during the reign of Terror. The reader is projected into a work of artistic fiction where the real and the imaginary coalesce vertiginously. Michon plays with fiction, risking its conventions and boundaries within a strategy of fake.